A nano curcumin–multi-walled carbon nanotube composite as a fluorescence chemosensor for trace determination of celecoxib in serum samples. Issue 46 (15th November 2022) - Pourreza, Nahid; Zargar, Behrooz; Hoveizavi, Reza
Abstract : A novel method was developed for trace determination of celecoxib by monitoring its quenching effect on fluorescence intensity of curcumin nanoparticles loaded on multi-walled carbon nanotubes–COOH (Cur–MWCNT–COOH) composite. Abstract : A novel method is presented here for trace determination of celecoxib by fluorescence detection using curcumin nanoparticles (CurNPs) loaded on multi-walled carbon nanotubes with carboxyl functional groups (CurNPs–MWCNT–COOH). For the synthesis of CurNPs–MWCNT–COOH, CurNPs were retained on carbon nanotubes with the aid of ultrasound waves. The sensing method is based on monitoring the quenching of synthesized CurNPs–MWCNT–COOH fluorescence by celecoxib. The morphology of CurNPs–MWCNT–COOH was studied by transmission electron microscopy (TEM) of the composite alone and in the presence of celecoxib. The effects of several parameters on the production of CurNPs–MWCNT–COOH and determination of celecoxib such as the Triton X-100 concentration, the amount of MWCNT–COOH and the pH were evaluated and optimum conditions were established. The calibration graph was found to be linear in the range of 20–220 ng mL −1 for celecoxib in the initial solution. The detection limit based on three times the standard deviation of the blank was 5.8 ng mL −1 for celecoxib and relative standard deviations (RSD) of 3.6% and 1.8% were obtained for eight replicate determinations of 60 ng mL −1 and 180 ng mL −1 of celecoxib, respectively. The method was applied to the determination of celecoxib in serum samples.